Survival after wedge resection versus lobectomy for stage IA second primary NSCLC with previous lung cancer-directed surgery - Song, Congkuan; Lu, Zilong; Li, Donghang; Pan, Shize; Li, Ning; Geng, Qing (Frontiers in Oncology, 2022)
Background: The surgical procedure for early-stage second primary non-small cell lung cancer (SP-NSCLC) remains controversial, especially for patients with previous lung cancer-directed surgery. This study aims to compare the survival after wedge resection and lobectomy for these patients. Methods: Stage IA SP-NSCLC patients with clear clinical information were searched from the Surveillance, Epidemiology, and End Results (SEER) database. Cox proportional hazard model, competing risk model and Kaplan-Meier survival curve were used to describe the survival difference between wedge resection and lobectomy. A 1:1 propensity score matching (PSM) method was also performed to reduce the potential impact of confounding factors between the two groups. Results: Of the 320 eligible stage IA SP-NSCLC patients included in this study, 238 (74.4%) patients underwent wedge resection and 82 (25.6%) patients received lobectomy. The 5-year overall survival (OS) was 61.3% with wedge resection and was 66.1% with lobectomy. Both before and after PSM, wedge resection showed similar OS and lung cancer specific mortality as lobectomy in the entire cohort. Additionally, in all subgroup analyses, wedge resection demonstrated equivalent survival to lobectomy. However, in the female, sub-lobectomy for the first primary lung cancer, and interval ≤ 24 months subgroups, wedge resection displayed a higher lung cancer specific mortality than lobectomy (fine-gray test, all p < 0.05). Conclusion: Overall, wedge resection is comparable to lobectomy in OS for stage IA SP-NSCLC patients with previous lung cancer-directed surgery. Therefore, we believe that wedge resection may be sufficient for these patients, although in some cases, wedge resection has a higher lung cancer-specific mortality rate than lobectomy.